Supporting political stability by strengthening local government: Decentralisation in Ukraine - Lily Salloum Lindegaard; Neil Webster (Danish Institute for International Studies (DIIS), 2018)
The government that followed the 2014 Maidan revolution in Ukraine has pushed a decentralisation agenda. After decades of Soviet style top-down governance, the status and role of local governments - hromadas - has been pushed to the fore. If implemented successfully, it could increase local development and political engagement, ultimately contributing to increased political stability in Ukraine and Europe. Yet the significance of decentralization reforms is often lost in the noise surrounding Crimea, the secessionist conflict in the east, and the political power struggles in Kiev. For legal reasons, the current decentralisation process is "voluntary", with local communities having to agree to the changes. This has introduced unintended challenges, but also a bottom-up political dynamic to the process. At the same time, uncertainty and opposition to decentralisation reforms remain, perhaps understandable given a rapidly shifting political and legal landscape, the diverse political and personal interests involved, and the fear of political fragmentation that could benefit Russia. Denmark is one of several EU countries supporting the reform process. This DIIS Report focuses in on the processes unfolding in local communities and political arenas, affecting peoples' lives, their hopes, and their relationship to the state from local to national level.
Keywords: 300